Cumin-Harvesting Mechanization of the Xinjiang Cotton–Cumin Intercropping System: Review of the Problem Status and Solutions - Sheng Tai; Zhong Tang; Bin Li; Shiguo Wang; Xiaohu Guo (Agriculture)
Cumin (Cuminum cyminum L.) is a globally important spice crop, particularly significant in Xinjiang, China, where it is extensively cultivated in cotton–cumin intercropping systems. This review concentrates on the serious bottleneck hindering the development of the cumin industry: the low level of harvesting mechanization. Traditional manual harvesting methods are labor-intensive, inefficient, and result in high yield losses. This paper fully explores the prospects and challenges of mechanizing cumin harvesting in accordance with the particular biological characteristics of cumin plants and the complexity of intercropping systems. We review the current status of research in the following domains: (1) cumin biological traits and intercropping models; (2) grain loss and stalk damage patterns in stripper harvesting of similar crops; (3) factors influencing root–soil interaction during mechanical extraction; (4) uprooting–conveying harvesting techniques and row division/plant singulation methods applicable to root and tuber crops; and (5) cumin-threshing and -cleaning technologies. This review highlights the inadequacy of current grain-harvesting machinery for cumin and underscores the urgent need for specialized, low-loss harvesting technologies tailored to cumin’s delicate nature and intercropping context. Finally, we propose future research directions to overcome these mechanization challenges and promote the sustainable development of the cumin industry.